Biomarkers for visceral hypersensitivity in patients with irritable bowel syndrome. Issue 12 (3rd July 2017) - Mujagic, Z.; Jonkers, D. M. A. E.; Ludidi, S.; Keszthelyi, D.; Hesselink, M. A.; Weerts, Z. Z. R. M.; Kievit, R. N.; Althof, J. F.; Leue, C.; Kruimel, J. W.; van Schooten, F. J.; Masclee, A. A. M.
Abstract: Background: Increased visceral sensitivity is observed in up to 60% of patients with Irritable Bowel Syndrome (IBS). Mucosal inflammation, altered neuroendocrine activity and intraluminal metabolic processes may contribute to the development of visceral hypersensitivity. Previously, we demonstrated that biomarkers, indicative for these biological processes, were altered in IBS patients compared to healthy controls. However, how these processes relate to visceral hypersensitivity is unknown. Aim: The aim of this study was to provide insight in biological processes associated with visceral hypersensitivity. Fecal and plasma biomarkers were measured in normosensitive and hypersensitive IBS patients. Methods: A total of 167 IBS patients underwent a rectal barostat procedure to assess visceral sensitivity to pain. Based on the outcome, patients were classified into a normosensitive or hypersensitive group. Calprotectin, human β‐defensin 2 (HBD2), chromogranin A (CgA), and short chain fatty acids (SCFAs) were measured in feces, citrulline in plasma, and serotonin and its main metabolite 5‐hydroxyindoleacetic acid (5‐HIAA) in platelet‐poor plasma. Key Results: Fecal markers and plasma citrulline were measured in 83 hypersensitive and 84 normosensitive patients, while platelet‐poor plasma for the assessment of serotonin and 5‐HIAA was available for a subgroup, i.e. 53 hypersensitive and 42 normosensitive patients. No statistically significant differences were found in concentrations of biomarkers between groups. Adjustment of the analyses for potential confounders, such as medication use, did not alter this conclusion. Conclusions & Inferences: Our findings do not support a role for the biological processes as ascertained by biomarkers in visceral hypersensitivity in IBS patients. This study is registered in the US National Library of Medicine (clinicaltrials.gov, NCT00775060).